Added Bonus? The Relationship Between California School Districts' Specialized Teacher Staffing Needs and the Use of Economic Incentive Policies. (March 2015) - Strunk, Katharine O.; Zeehandelaar, Dara B.
In this paper, we explore the use and efficacy of fiscal incentive policies in California school districts. We ask whether districts with high need for teachers with English as a second language (ESL) or special education credentials are more likely to implement incentives targeting these teachers. We find mixed evidence that districts align their incentives with their staffing needs. We conclude by discussing possible rationales for our results.